2022
DOI: 10.21608/ijthm.2022.270132
|View full text |Cite
|
Sign up to set email alerts
|

The Intention of Applying Digital Entrepreneurship (De) Among Undergraduate Tourism Students in Egypt

Shaymaa El-Sisi

Abstract: Entrepreneurship is an economic tool that aims to enhance people's lives. Digital entrepreneurship is one of the latest theories that academic research tries to cover. This study examines the factors that influence undergraduate tourism students to apply digital entrepreneurship. Despite the presence of several studies that tackled different aspects of entrepreneurship in Egypt, there is limited research about applying digital entrepreneurship, especially among undergraduate tourism students. So, the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…This assertion resonates with the findings of Suparno et al, (2020), who illuminated a positive correlation between students' aspirations for digital business ventures and their creativity and digital literacy levels. In alignment with that, the following studies also found a positive correlation between entrepreneurship intention and digital literacy across diverse contexts (EL-SISI, 2022;Hardika et al, 2022). Therefore, the following hypothesis was investigated: H2: Digital Literacy influences the digital entrepreneurial intentions (DEI) of undergraduate students in Jordan.…”
Section: Digital Literacymentioning
confidence: 76%
“…This assertion resonates with the findings of Suparno et al, (2020), who illuminated a positive correlation between students' aspirations for digital business ventures and their creativity and digital literacy levels. In alignment with that, the following studies also found a positive correlation between entrepreneurship intention and digital literacy across diverse contexts (EL-SISI, 2022;Hardika et al, 2022). Therefore, the following hypothesis was investigated: H2: Digital Literacy influences the digital entrepreneurial intentions (DEI) of undergraduate students in Jordan.…”
Section: Digital Literacymentioning
confidence: 76%
“…Analysis of students' profiles showed their proficiency in digital literacy and familiarity with internet tools. However, a small percentage of students can create web pages that serve as digital tools [14].…”
Section: Consequences Constructsmentioning
confidence: 99%